Perbahasan Tentang Takdir: Dawabit dan Sorotan Literatur: Discussion on Taqdir: Dawabit and Literature Review - Mohd Azhar, Muhammad Hazim; Syed Abdul Rahman, Syed Mohammad Hilmi (Online Journal of Research in Islamic Studies, 2017)
Al-Taqdir is one of the things that God has kept obscure. It should be understood from the Quran and al-Hadith which is guided by the understanding of the scholars as it is not something that will be easily accepted by our logical mind and senses. There are several hadiths and views of Islamic scholars that prohibit debates and exploration in details on the matter of fate. Nonetheless, there are also views that permits it and at the same time make it as compulsory discussion. With regard to this matter, this study attempts to discuss on the question of destiny, the principles concern in debating about destiny and highlighting the previous studies on it. The method used in this study to collect data is through documentation. Based on the surveys of studies done on the concept of destiny, many aspects have been evaluated, some even associate it with a branch of modern disciplines such as psychology. This proves that the discussions on fate is allowed in accordance with the guidelines that has been established by the scholars.